Incidence of antibodies to protamine sulfate/heparin complexes in cardiac surgery patients and impact on platelet activation and clinical outcome - Pouplard, Claire; Leroux, Dorothée; Rollin, Jérome; Amiral, Jean; May, Marc-Antoine; Gruel, Yves (Thrombosis and Haemostasis, 2013)
A new ELISA (Zymutest HIA®), based on incubation of diluted plasma with protamine/heparin (PRT/H) complexes without and with platelet factor 4 (PF4) provided by a platelet lysate, was used to detect heparindependent antibodies in a cohort of 232 cardiac surgery (CS) patients and in 47 patients with heparin-induced thrombocytopenia (HIT). Significant binding of IgG/A/M to PRT/H complexes was demonstrated in 59 CS patients (25.4%), with similar absorbances whether platelet lysate was added to the plasma or not, and significant reactivity to PF4/H in 29 of them. Antibodies to PRT or heparin alone were present in 15 and two of these patients, respectively. Importantly, antibodies to PRT/H were detected in only three of the 47 HIT patients, who had also undergone recent CS. The Zymutest HIA® was positive in another 41 CS patients (17%), but only or mainly when their plasma was tested with platelet lysate, with significant levels of antibodies to PF4/H in 40 of them without detectable reactivity to PRT or heparin alone. Slight antibody binding to PRT/H complexes was also measured in six of these 41 patients. Therefore, a total of 35 CS patients exhibited dual antibody reactivity towards PRT/H and PF4/H complexes. Serotonin release assay performed with PRT alone was positive in 17 CS patients with antibodies to PRT/H, but all had normal platelet count evolution without thrombosis postoperatively. In conclusion, antibodies to PRT/H are frequently present in CS patients postoperatively (25.4%), and can activate platelets in vitro, but their clinical impact remains questionable.
Keywords: Cardiac surgery; Protamine; Heparin-dependent antibodies; Heparin-induced thrombocytopenia